Costs and Cost Drivers of Providing Option B+ Services to Mother-Baby Pairs for PMTCT of HIV in Health Centre IV Facilities in Jinja District, Uganda. (20th May 2020) - Mukose, Aggrey D.; Kebede, Senait; Muhumuza, Christine; Makumbi, Fredrick; Komakech, Henry; Bayiga, Esther; Busobozi, Denis; Musinguzi, Joshua; Kuznik, Andreas; Stegman, Peter; Forsythe, Steven; Kagaayi, Joseph
Abstract : Background . In 2013, the World Health Organization (WHO) revised the 2012 guidelines on use of antiretroviral drugs (ARVs) for the prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV). The new guidelines recommended lifelong antiretroviral therapy (ART) for all HIV-positive pregnant and breastfeeding women irrespective of CD4 count or clinical stage (also referred to as Option B+). Uganda started implementing Option B+ in 2012 basing on the 2012 WHO guidelines. Despite the impressive benefits of the Option B+ strategy, implementation challenges, including cost burden and mother-baby pairs lost to follow-up, threatened its overall effectiveness. The researchers were unable to identify any studies conducted to assess costs and cost drivers associated with provision of Option B+ services to mother-baby pairs in HIV care in Uganda. Therefore, this study determined costs and cost drivers of providing Option B+ services to mother-baby pairs over a two-year period (2014–2015) in selected health facilities in Jinja district, Uganda. Methods . The estimated costs of providing Option B+ to mother-baby pairs derived from the provider perspective were evaluated at four health centres (HC) in Jinja district. A retrospective, ingredient-based costing approach was used to collect data for 2014 as base year using a standardized cost data capture tool. All costs were valued in United States dollars (USD) using the 2014 midyear exchange rate. Costs incurred in the second year (2015) were obtained by inflating the 2014 costs by the ratio of 2015 and 2014 USA Gross Domestic Product (GDP) implicit price deflator. Results . The average total cost of Option B+ services per HC was 66, 512.7 (range: 32, 168.2–102, 831.1) USD over the 2-year period. The average unit cost of Option B+ services per mother-baby pair was USD 441.9 (range: 422.5–502.6). ART for mothers was the biggest driver of total mean costs (percent contribution: 62.6%; range: 56.0%–65.5%) followed by facility personnel (percent contribution: 8.2%; range: 7.7%–11.6%), and facility-level monitoring and quality improvement (percent contribution: 6.0%; range: 3.2%–12.3%). Conclusions and Recommendations . ART for mothers was the major cost driver. Efforts to lower the cost of ART for PMTCT would make delivery of Option B+ affordable and sustainable.